Why crime?: an interdisciplinary approach to explaining criminal behavior - Robinson, Matthew B. (Carolina Academic Press, 2020)
"This book reviews the very latest empirical evidence with regard to the risk factors that produce antisocial and criminal behavior. The authors meaningfully integrate risk factors identified by more than a dozen academic disciplines that increase the odds of antisocial behavior and criminality. The result is a new interdisciplinary theory that helps break down traditional barriers and overcomes the "disciplinary myopia" that plagues criminological theory. Unlike the typical criminological theory text, this book actually advances the state of criminological theory as well as the field of criminology"--